Topical Issues of Accounting of Leasing Transactions in Terms of International Financial Reporting Standards - Ryabchenko, Anastasiya Valerievna; Shmatova, Elena Vladimirovna; Pazderova, Victoria Yuryevna; Tkhagapso, Ruslan Aslancherievich; Khot, Fatima Teuchezhevna (International Journal of Economics and Financial Issues, 2016)
Rental transactions play a very prominent role in property relations of many Russian enterprises and vary widely. Along with traditional rental services, their new forms also continue to develop in recent years, which is first of all leasing. However, in a challenging economic environment that objectively led to the decline of leasing transactions, there are a number of factors that contribute to the preservation of the interest of the business community. The article examines the modern approaches to accounting practice of leasing operations based on the current institutional framework. Due to the increasing interest in international leasing deals, the methodological approaches to recording the main operations of the lessee under the lease contract in accounting are offered, based on the requirements of international standards. Given the increased interest of external users to accounting due to the benefits provided by the practical application of International standards, as well as the need to increase the investment attractiveness of Russian companies, these provisions cause doubtless interest of all market participants to IFRS and determine the relevance of the proposed article. Keywords: leasing, international standards of financial accounting and reporting, operating lease, financial lease. JEL Classifications: G32, M41.